Editorial: New insights in thyroid and Covid-19 - Sgarbi, Jose Augusto (2022)
The Coronaviruses Disease 2019 (Covid-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is perhaps the most dramatic threat to human health since the Spanish flu in 1918. Almost 700 million cases and more than 6 million deaths have been reported worldwide by November 20, 2022 (1). The lung is the main affected organ, and the most critical clinical presentation has been characterized by interstitial pneumonia, acute respiratory distress syndrome, multiple organ failure, and death (2). Multiple endocrine organs, such as the pituitary, pancreas, adrenal, gonads, and thyroid gland, have also been affected (3). Detrimental effects on thyroid function have been reported in patients with and without pre-existing thyroid disease. Nonthyroidal illness syndrome (NTIS), subacute thyroiditis (SAT), Hashimoto’s thyroiditis, and Graves’ disease have been the most frequent thyroid dysfunctions associated with Covid-19 (4). Two major pathophysiological models have been implicated, a direct effect by virus attack causing follicular cells damage and an indirect effect caused by an immune-inflammatory abnormal response to the virus (5). Most recently, thyroid autoimmune diseases have also been reported following Covid-19 vaccination (6).